Ethical Implications of Artificial Intelligence (AI) in Healthcare - Dr. Smitha V Shenoy, Dr. Govindaraj Pandith T G, Tejus B (Journal of Neonatal Surgery, 2025)
The proliferation of AI systems across various domains raises significant ethical questions that demand careful consideration. This exploration delves into the ethical dimensions associated with the widespread adoption of artificial intelligence in Health care sector. This study seeks to unravel the ethical intricacies of AI through an interdisciplinary approach, drawing from philosophy, technology ethics, law, and social sciences. By examining case studies, ethical frameworks, and expert perspectives, we aim to provide a holistic understanding of AI's ethical implications. The objectives of the study are to assess the level of knowledge and awareness among Medical Practitioners regarding artificial intelligence (AI) technologies in the field of medicine and healthcare, to explore Medical Practitioners' attitudes, perceptions, and opinions toward the use of AI in various aspects of medical practice, such as diagnosis, treatment planning, and patient care and to identify and analyze the ethical implications of AI as perceived by Medical Practitioners in the medical field. In this study, a descriptive research design is employed to provide a comprehensive and detailed account of doctors' perceptions of artificial intelligence (AI) in medicine and to explore the ethical implications associated with its widespread adoption. The study reveals a multifaceted landscape of opinions within the medical community regarding AI's integration into Indian healthcare. While a notable segment of medical professionals expresses confidence in AI's potential, others emphasize the need for caution and ethical considerations. There is an underlying consensus that AI could contribute positively to healthcare efficiency and diagnostic accuracy. However, maintaining the human touch, empathy, and ethical standards of medical practice is essential.